Trash to treasure: Integrating waste management and financial literacy for sustainable behaviors - Kesuma, Muhammad Ramadhani; Wijaya, Stephanie; Putri, Alya Salsabilla (Priviet Social Sciences Journal, 2025)
The "Trash to Cash: Jago Atur Uang, Jago Rawat Bumi" program, conducted at SDN 008 Waru, Penajam Paser Utara Regency, East Kalimantan, Indonesia, aimed to enhance sixth-grade students’ understanding of waste management and financial literacy through an interactive educational intervention. Targeting 30 students aged 11–12 years, the program integrated the eco-financial concept, transforming inorganic waste, such as plastic bottles and cardboard, into economic assets via waste banks, with proceeds encouraging savings habits. Employing an action research approach, the intervention utilized presentations, the "Tebak Sampah" game, and a waste value calculation quiz. The results demonstrated a significant increase in waste classification knowledge (from 40% to 85% accuracy), with 95% of students recognizing the economic value of recyclables and 80% accurately calculating waste-derived income. Qualitative findings indicated high engagement and intention to collect recyclables, suggesting potential behavioral changes toward sustainability. Challenges, including time constraints and classroom management, did not diminish the program’s success in achieving its goals. This study contributes a novel framework for integrating environmental and financial education, offering a replicable model for primary schools to support the sustainable development goals.